ANALYSIS THE DISTRIBUTION AND POTENTIAL OF TOURISM OBJECT IN NGARGOYOSO DISTRICT, KARANGANYAR REGENCY - Chatarina Muryani; Sigit Santoso; Singgih Prihadi (GeoEco, 2019)
The purpose of this study was to analyze the distribution and potential of tourism objects found in Ngargoyoso District, Karanganyar Regency, Central Java Province. Ngargoyoso sub-district was chosen as the location of the study because in this area the development of tourism was very fast. Methods of data collection by field observations (penitikan tourist location using GPS), secondary data analysis and interviews with managers / tourists. The results showed that in Ngargoyoso Subdistrict there were 19 tourism objects scattered in four villages, namely Berjo, Girimulyo, Segorogunung and most of them in Kemuning Village. The results of the analysis of tourism potential indicate the potential of tourism objects in Ngargoyoso District consists of 3 categories of objects, namely tourism objects with the category of Very Potential (Tahura, Jumog Waterfall, and Parang Ijo Waterfall). Quite Potential category (Sukuh Temple, Telaga Madirda, Paragliding, Bukit Kemuning, Katresnan Valley, Sumilir Valley, Tanggri Asri, Kali Pucung, Taman Pesona, Jambu Merah "234", Taman Bintang, Kali Sebendo, Kalimas, Njurang Salam and Tubing Goa Sari ), the Less Potential category is the Planggatan Site.